Hepatoprotective Effect of Grape Seed and Skin Extract Against Lithium Exposure Examined by the Window of Proteomics - Ali Mezni; Olfa Khazri; Frédérique Jarnier; Julie Hardouin; Ferid Limam; Thierry Jouenne; Ezzeddine Aouani; Pascal Cosette (SAGE Publishing, 2022)
Context The liver is the organ by which the majority of substances are metabolized, including psychotropic drugs. Lithium (Li) used as drug for many neurological disorders such as bipolar disorders. Objective This study aims to assess lithium toxicity and to evaluate the hepatic-protective properties of a grape skin seed and extract (GSSE). Materials and methods Twenty-four male Wistar rats were exposed for 30 days to either various lithium concentrations, GSSE alone, or lithium supplemented with GSSE. The proteomic analysis revealed alterations of liver protein profiles after lithium treatments that were successfully identified by mass spectrometry. Results Lithium treatment induced an oxidative damage by the alteration of antioxidant enzymes activities such as superoxide dismutase, CAT, and Gpx. The regulated proteins are mainly involved in the respiratory electron transport chain, detoxification processes, ribosomal stress pathway, glycolysis, and cytoskeleton. Proteins were differentially expressed in a dose-dependent manner. Interestingly, GSSE reversed the situation and restored the level of liver proteins whose abundance was modified after lithium treatment, arguing for its protective activity. Conclusion Our data demonstrated the ability of proteomic analysis to underline the toxicity mechanisms of lithium in animal models. Based on these results, GSSE may be envisaged as a nutritional supplement to weaken the liver toxicity of lithium.